Personalized microbiome-driven effects of non-nutritive sweeteners on human glucose tolerance - Suez, Jotham; Cohen, Yotam; Valdés-Mas, Rafael; Mor, Uria; Dori-Bachash, Mally; Federici, Sara; Zmora, Niv; Leshem, Avner; Heinemann, Melina; Linevsky, Raquel; Zur, Maya; Ben-Zeev Brik, Rotem; et al. (Cell, 2022)
Non-nutritive sweeteners (NNS) are commonly integrated into human diet and presumed to be inert; however, animal studies suggest that they may impact the microbiome and downstream glycemic responses. We causally assessed NNS impacts in humans and their microbiomes in a randomized-controlled trial encompassing 120 healthy adults, administered saccharin, sucralose, aspartame, and stevia sachets for 2 weeks in doses lower than the acceptable daily intake, compared with controls receiving sachet-contained vehicle glucose or no supplement. As groups, each administered NNS distinctly altered stool and oral microbiome and plasma metabolome, whereas saccharin and sucralose significantly impaired glycemic responses. Importantly, gnotobiotic mice conventionalized with microbiomes from multiple top and bottom responders of each of the four NNS-supplemented groups featured glycemic responses largely reflecting those noted in respective human donors, which were preempted by distinct microbial signals, as exemplified by sucralose. Collectively, human NNS consumption may induce person-specific, microbiome-dependent glycemic alterations, necessitating future assessment of clinical implications.